2015
DOI: 10.1681/asn.2013121326
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin-Induced Phosphatidylinositol-4-Phosphate 5-Kinase Diffusion from Microvilli Stimulates ROMK Channels

Abstract: We recently showed that lovastatin attenuates cyclosporin A (CsA)-induced damage of cortical collecting duct (CCD) principal cells by reducing intracellular cholesterol. Previous studies showed that, in cell expression models or artificial membranes, exogenous cholesterol directly inhibits inward rectifier potassium channels, including Kir1.1 (Kcnj1; the gene locus for renal outer medullary K + [ROMK1] channels). Therefore, we hypothesized that lovastatin might stimulate ROMK1 by reducing cholesterol in CCD ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 48 publications
(62 reference statements)
2
19
0
Order By: Relevance
“…which are Cho-rich microdomains are mainly located in microvilli [13], these data suggest that CCD cells can synthesize Cho and that Cho accumulates in microvilli with PIP 2 to form a unique membrane microdomain to regulate ENaC activity.…”
Section: Mβcd and Lovastatin Reduce Cho And Pip 2 In The Microvillimentioning
confidence: 68%
See 4 more Smart Citations
“…which are Cho-rich microdomains are mainly located in microvilli [13], these data suggest that CCD cells can synthesize Cho and that Cho accumulates in microvilli with PIP 2 to form a unique membrane microdomain to regulate ENaC activity.…”
Section: Mβcd and Lovastatin Reduce Cho And Pip 2 In The Microvillimentioning
confidence: 68%
“…Another exciting discovery is that extraction of Cho out of the outer leaflet of the apical membrane with MβCD induces Madin-Darby canine kidney cells to lose their microvilli [12]. We have recently shown that MβCD can also excise the microvilli of CCD principal cells to release vesicles from the apical membrane [13]. These studies together suggest a hypothesis that depletion of the outer leaflet Cho may reduce ENaC density by destruction of the microvilli.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations